Low immunogenicity of emicizumab in persons with haemophilia A. Issue 6 (4th September 2021) - Schmitt, Christophe; Emrich, Thomas; Chebon, Sammy; Fernandez, Elena; Petry, Claire; Yoneyama, Koichiro; Kiialainen, Anna; Howard, Monet; Niggli, Markus; Paz‐Priel, Ido; Chang, Tiffany
Abstract: Introduction: Emicizumab is a humanised, bispecific monoclonal antibody mimicking the cofactor function of activated factor (F)VIII. It is indicated for routine prophylaxis of bleeding episodes in persons with haemophilia A (PwHA) with/without FVIII inhibitors. Aim: To evaluate the development of anti‐emicizumab antibodies and their impact on pharmacokinetics (PK), pharmacodynamics (PD), efficacy and safety in PwHA. Methods: Data from seven completed or ongoing phase 3 studies were pooled. The assessment of the immunogenicity profile of emicizumab included anti‐drug antibody (ADA) measurement and the association of ADAs with PK, PD, bleeding events, and adverse events. Results: Of 668 PwHA evaluable for immunogenicity analysis, 34 (5.1%) developed ADAs after exposure to emicizumab. ADAs were transient in 14/34 PwHA (41.2%). ADAs were neutralising in vitro in 18/34 PwHA (52.9%) and associated with decreased emicizumab concentration in 4/668 evaluable PwHA (.6%); of those, one (.1%) discontinued emicizumab due to loss of efficacy. ADAs without decreased exposure did not impact emicizumab efficacy. The proportion of PwHA who had injection‐site reactions (ISRs) was higher in ADA‐positive PwHA (29.4% vs. 20.8%); however, the safety profile was similar between ADA‐positive and ADA‐negative PwHA, overall. No cases of anaphylaxis or hypersensitivity were reported in ADA‐positive participants. Conclusion: The immunogenicity risk of emicizumab in phase 3 studies was low. ADAs, including in vitro neutralising ADAs, were not associated with a change in safety profile. Routine surveillance is, therefore, not warranted; however, in cases where a loss and/or waning of efficacy are observed, prompt evaluation by a healthcare provider should be sought.